PENGARUH IMPLEMENTASI DAN KARAKTERISTIK INOVASI SMM ISO 9001 : 2000 Terhadap kepuasan staf pada inovasi SMM ISO ISO 9001 : 2000 DI LPMP Provinsi Kalimantan Barat - Rita, Darnila (2012)
Innovation in quality management system which will be applied within an organization depends on those individuals in that organization. The current quality management system ISO 9001:2000 that adopted by Kalimantan Barat LPMP comes from the policy of MONE (Ministry of National Education). The success of this quality management system application depends a lot on the individual who work it out. Innovation which is not based on individual awareness neither prior to staffs education, will face the probability of necessity and will appear as obligation fullfilness only. This condition, further, will lead to unsatisfaction of application of that innovation and will influence the sustainability of using such innovation. Kalimantan Barat LPMP had adopted SMM ISO 9001:2000 in 2008 - 2009, yet ended it in 2010. Based on that fact, the research about the influence of innovation implementation and characteristic toward staff's satisfaction of SMM ISO 9001:2000 innovation, is needed. Therefor, this research is done, which aim to find out that influence of innovation implementation and characteristic toward staff's satisfaction of SMM ISO 9001:2000 innovation. Population of this research is the entire 92 staffs of Kalimantan Barat LPMP with 75 persons of sample. Data gathering is done with cluster stratified random sampling technic, using quistioner and analized with correlation analysis, simple regression and multiple regression. The result of this research shows that 1) there is an influence of innovation implementation toward staff's satisfaction of SMM ISO 9001:2000 innovation with moderate level, 2) there is an influence of innovation characteristic toward staff's satisfaction of SMM ISO 9001:2000 innovation with poor level, 3) innovation implementation influences significantly staff's satisfaction of SMM ISO 9001:2000, yet innovation characteristic doesn't. Recommendation that come from this research is that consistency of quality management system implementation, need to be increased, as agreed before to gain a satisfy result, also education and comprehension enhancement toward the current innovation in order to achieve positive characteristic anad satisfaction of that innovation. Keywords : implementation of SMM ISO 9001:200, characteristic of SMM ISO 9001:2000 and staff's satisfaction of that SMM ISO 9001:2000 innovation.